2021
DOI: 10.1038/s41598-021-81120-y
|View full text |Cite
|
Sign up to set email alerts
|

Soil microbial properties of subalpine steppe soils at different grazing intensities in the Chinese Altai Mountains

Abstract: Long-term provision of ecosystem services by grasslands is threatened by increasing stocking densities. The functions of grassland ecosystems depend on a mutual relationship between aboveground and belowground biota. While the effects of increasing stocking density on plant biomass are well studied, little is known about its impact on soil microbial properties. To fill this knowledge gap a grazing experiment was conducted on a summer pasture in the Chinese Altai Mountains during the summers of 2014 and 2015 us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…This study found that grazing evidently elevated the SH ( Shan et al, 2011 ; Zhang et al, 2019 ; Li et al, 2021 ; Liu et al, 2021 ), BD, pH ( Blank et al, 2006 ; Ajorlo et al, 2011 ; Rong et al, 2022 ), ACa, AMg ( Jusoff, 1988 ; Blank et al, 2006 ), ßGC, ACP, and C limitation ( Goenster-Jordan et al, 2021 ), but decreased the WC and AP ( Niu et al, 2016 ; Sigcha et al, 2018 ; Chen et al, 2021 ; Fenetahun et al, 2021 ; Rong et al, 2022 ; Figure 1 ). The buffalo squeezed the soil pores that include those pores originally storing water and air, through treading, which caused soil compaction ( Ludvíková et al, 2014 ), elevated the bulk density ( Li et al, 2008 ; Zhan et al, 2020 ; Fenetahun et al, 2021 ; Wade et al, 2022 ) and soil hardness, and reduced soil water infiltration ( Daniel et al, 2002 ).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…This study found that grazing evidently elevated the SH ( Shan et al, 2011 ; Zhang et al, 2019 ; Li et al, 2021 ; Liu et al, 2021 ), BD, pH ( Blank et al, 2006 ; Ajorlo et al, 2011 ; Rong et al, 2022 ), ACa, AMg ( Jusoff, 1988 ; Blank et al, 2006 ), ßGC, ACP, and C limitation ( Goenster-Jordan et al, 2021 ), but decreased the WC and AP ( Niu et al, 2016 ; Sigcha et al, 2018 ; Chen et al, 2021 ; Fenetahun et al, 2021 ; Rong et al, 2022 ; Figure 1 ). The buffalo squeezed the soil pores that include those pores originally storing water and air, through treading, which caused soil compaction ( Ludvíková et al, 2014 ), elevated the bulk density ( Li et al, 2008 ; Zhan et al, 2020 ; Fenetahun et al, 2021 ; Wade et al, 2022 ) and soil hardness, and reduced soil water infiltration ( Daniel et al, 2002 ).…”
Section: Discussionmentioning
confidence: 69%
“…The returns of ACa and AMg in form of dung and urine ( Saunders, 2012 ) and accelerated soil weathering by grazing ( Lin et al, 2021 ) could elevate the availability of calcium and magnesium, which, in turn, are conducive to improving soil pH ( Figure 1C ). Decreases in plant biomass and coverage ( Wang and Tang, 2019 ; Lin et al, 2021 ) and removal of aboveground biomass by buffalo eating and treading, and root biomass ( Wade et al, 2022 ) due to the depletion of soil water content, and increased bulk density ( Lin et al, 2021 ) and soil hardness ( Figure 1A ), generally reduced the C inputs, which, in turn, commonly reduced the bioavailable soil C ( Ravhuhali and Moyo, 2021 ), aggravated C limitation ( Goenster-Jordan et al, 2021 ) as indicated by the increased investment in C-capturing enzyme (ßGC, Figure 1H ), which can hydrolyze sugars and release labile C. The vector angle under ungrazed was <45, indicating that the soil microbial communities were limited by N; the vector angle under grazed crossed with 45, indicating that the soil microbial communities were under N and P co-limitation. This showed that grazing shifted soil microbial communities from under N limitation to under NP limitation.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are similar to what was reported from a Mediterranean grassland in Israel (Li et al, 2005). Other studies using laboratory incubations, however, detected a decrease in MMQ due to an increase in MBC (Goenster‐Jordan et al, 2021; Raiesi & Riahi, 2014) or an increase in MMQ due to an increase in MR in grazed plots (Aldezabal et al, 2015). When MR was measured in the field via trenching or whole plant removal, again higher MR and therefore a decrease in MMQ was reported from grazed plots (Li et al, 2013; Wang, Liu, et al, 2020; Zhang et al, 2015; Zhou et al, 2019).…”
Section: Discussionmentioning
confidence: 96%
“…These latter findings were explained by higher temperature sensitivities of MR and higher soil organic C concentrations due to increased plant biomass and plant litter input in ungrazed grasslands (Li et al, 2013; Wang, Liu, et al, 2020; Yunbo Wang, Wang, et al, 2020; Zhang et al, 2015). The most likely reason for the divergent findings of herbivore exclusion on MMQsoil, MR and MBC in the literature could be related to differences in grazing intensities between studies (Goenster‐Jordan et al, 2021; Jiang et al, 2020), the herbivore species present, their variation in body size or functional type (Risch et al, 2013; Sitters, Kimuyu, et al, 2020), differences in the soil or microbial community composition (e.g., Peschel et al, 2015; Stark et al, 2012; Wang et al, 2019) or C : N : P stoichiometry across grasslands (e.g., Roy & Bagchi, 2021; Yu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, scholars have paid much attention to the water-resource and environmental problems in the western part of the Tianshan [10,11] and Altay [12,13] Mountains (Mts. ), and among these, the soil problems [14][15][16] and overall water quantity of the rivers [17][18][19] in the regions of the Tianshan and Altay Mts. have been studied; however, there is still a lack of basic information on water quality.…”
Section: Introductionmentioning
confidence: 99%